Contribution of internet resources to mastery genetic concept on prospective teachers. (April 2020) - Maryuningsih, Y; Hidayat, T; Riandi, R; Rustaman, N Y
Abstract: The use of the internet and smartphones in learning is interdependence because of its function which provides various learning resources. This study aims to determine the role of the internet as a learning resource for prospective teacher on concepts mastery, using a correlation design with Pearson correlational statistical tests to describe and measure the degree of association between the two variables, namely the prospective duration of the online teacher and the acquisition of concepts. The subjects of this study were semester 5 (five) students majoring in biology education totalling 99 students at one of the university in West Java. The study was conducted on Genetic course in mobile learning with Gen 21 CS application in 3 (three) Genetic course activities. The results showed that online duration correlated with mastery of concepts. The highest correlation with a correlation value of 0.37 in the third activity, with the value of the level of significance of the category is low, which means that besides the duration of online there are other things that contribute to concept mastery.